Punished with love - Cartland, Barbara; Barbara Cartland (United states and Canada Bantam books, Inc., 1980)
In Punished with Love by Barbara Cartland, shy Latonia Hythe impersonates her flighty cousin, Toni, to travel to India with the stern Lord Branscombe, bypassing an arranged, unwanted marriage for Toni. Amidst the Raj's splendor, Latonia faces his disapproval, but discovers a dangerous plot against him, leading to romance.
English